Developing a Climate-Smart Village for Reduced Climate Risk and Food Insecurity in Daga-Birame, Senegal - Sanogo, Diaminatou; Camara, Baba Ansoumana; Diop, Mouhamadou; Ndiaye, Ousmane; Ky-Dembélé, Catherine; Bayala, Jules; Dayamba, Sidzabda Djibril; Zougmoré, Robert B.; Ouédraogo, Mathieu; Partey, Samuel T. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2016)
CSA initiatives aim to sustainably increase productivity, enhance resilience, and reduce/remove greenhouse gases (GHGs), and require planning to address trade-offs and synergies between these three pillars: productivity, adaptation, and mitigation (CIAT; BFS/USAID. 2016). The CSV concept reflects an ambition to improve the integration of agriculture development and climate responsiveness. It is an approach that requires site-spe- cific monitoring and assessments of the social, economic and environmental conditions to identify appropriate agricultural production technologies and practices. In the Daga-Birame village, an initial diagnosis using the TOP-SECAC toolkit (Somda et al., 2011) was conducted starting by an analysis of vulnerability and adaptation capacity to climate change. It entailed participatory drawing of a map on livelihood resources and climate hazards in order to locate them in the territory under the community management plan. Then a vulnerability matrix was developed to analyze the perception of village commu- nity members about the level of influence of climatic hazards on main livelihood resources. Finally, a matrix of adaptation strategies was used to help identify and analyze (current and future) adaptation strategies. It included the level of importance of main livelihood resources in the implementation of the defined strategies. This identification of local constraints and opportunities was key to designing the CSV of Daga-Birame. Based on the village vision of its future, a set of actions have been identified by the community in order to achieve the desired changes in agricultural productivity and food security, income genera- tion, resilience improvement and sustainable management of the environment in the village. These actions were structured around four components: Climate Information Services (CIS); development of climate-smart agriculture technologies/practices; village development planning and local knowledge and institutions.